Systemic Safety Analysis of Midblock Pedestrian Crashes in Massachusetts. Issue 11 (November 2022) - Gooch, Jeff; Hamilton, Ian; Polin, Bonnie; Tanzen, Riana; Cohen, Tal
Pedestrians are vulnerable road users on Massachusetts roadways, particularly at midblock crossings. To develop safety improvement projects to address pedestrian safety issues, Massachusetts Department of Transportation (MassDOT) conducted a systemic safety analysis of severe midblock pedestrian crashes. The analysis incorporated crash, roadway, transit, census, and equity data to identify roadway segments that showed the higher probability for a severe pedestrian crash. Based on overrepresentation, principal arterials, minor arterials, and major collectors were identified as focus facility types. Binomial logit regression was used to identify risk factors for each focus facility type. Risk factors included number of lanes, traffic volume, population density, commute behaviors, employment density, and measures of equity. The authors found consistent risk factors across the three focus facility types. Ultimately, MassDOT will use these results to prioritize sites for midblock pedestrian safety systemic improvements.